PENGARUH UKURAN PERUSAHAAN, LABA/RUGI PERUSAHAAN,KOMPLEKSITAS OPERASI PERUSAHAAN, DAN REPUTASI KAPTERHADAP AUDIT DELAY PADA PERUSAHAANPERTAMBANGAN - Jessica Tricia; Prima Apriwenni (Jurnal Akuntansi Bisnis, 2018)
The background of this research there were inconsistent results on the variables that affect audit delay. Besides that, in 2015 several companies suspended by the Stock Exchange because of late financial reports.This study aimed to research the influence of company size, company’s profit/loss, company’s operations complexity and reputation of public accountant firm on audit delay. This study has done at mining companies listed in Indonesian Stock Exchange during the period 2012-2014. The sampling method used purposive sampling and obtained 96 as total sample. Linear regression analysis is used as analysis technique. This research concluded that company’s profit/loss and reputation of public accountant firm negatively influenced on audit delay. Company size didn’t affect to audit delay. Company’s operations complexity was no conclusion.  Keywords :audit delay, company size, company’s profit/loss, company’s operations complexity,  reputation of public accountant firm.